Prevalencia de la colelitiásis en pacientes intervenidos quirúrgicamente en el Hospital Teófilo Dávila, de la ciudad de Machala, en el año 2007 - Serrano Olmedo, Wilman W. (2008)
The present investigation was carried out in the Hospital Teófilo Dávila, of the Machala city. The sample included the whole subject Cholecholitiasis payees to those who were practiced cholecystectomy in the period understood between January 1 and December 31 the 2007. The observed variable was the prevalence of the Cholecholitiasis in the practiced cholecystectomy